1999
DOI: 10.1046/j.1365-3156.1999.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies against hepatitis A and E viruses among rural populations of the Chaco region, south‐eastern Bolivia

Abstract: SummaryWe conducted a cross-sectional study to determine the seroprevalence of antibodies against hepatitis A and hepatitis E viruses (HAV and HEV) in the population of two rural areas, Camiri and Villa Montes, of the Chaco region, south-eastern Bolivia. HAV antibodies were detected in 461 (94.1%) of 490 serum samples tested, not differing significantly between sexes and study areas. The HAV seropositivity rate (64.7%) was high even in the youngest age group (1-5 years). The prevalence of HEV was 7.3%, with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
2
18
2
2
Order By: Relevance
“…The anti-HEV IgG prevalence according to sex, shows a higher rate among the male group. This finding could not be correlated with previous studies, which showed no statistical difference in the anti-HEV prevalence rate between males and females (Souto & Fontes 1998, Alvarez-Muñoz et al 1999, Bartolini et al 1999.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The anti-HEV IgG prevalence according to sex, shows a higher rate among the male group. This finding could not be correlated with previous studies, which showed no statistical difference in the anti-HEV prevalence rate between males and females (Souto & Fontes 1998, Alvarez-Muñoz et al 1999, Bartolini et al 1999.…”
Section: Discussioncontrasting
confidence: 99%
“…The highest anti-HEV IgG prevalence observed in the oldest age groups is according to results found in previous investigations (Balayan et al 1996, Alvarez-Muñoz et al 1999, Bartolini et al 1999. The anti-HEV IgG prevalence according to sex, shows a higher rate among the male group.…”
Section: Discussionsupporting
confidence: 79%
“…A study carried out by Bartoloni et al (1999) with rural populations in Bolivia showed a seroprevalence ranging from 4.4 to 10.4 % with no significant differences between genders. In Peru, although data regarding seroprevalence in general population do not exist, anti-HEV IgG was detected in 10.5% of the subjects comprising a risk group (Vildosola et al 2000).…”
Section: Seroprevalence In Humans and Pigsmentioning
confidence: 93%
“…This global decline in HAV endemicity has been observed mainly in countries with a human development index (HDI) >0.58 or a water coverage rate >55%. Since 2005, only three Latin American countries (Argentina, Panama, and Uruguay) have introduced [2][3][4]. HAV vaccinations into their routine immunization programs.…”
Section: Introductionmentioning
confidence: 99%
“…The observed seroprevalence in 5-year-old children ranged from high-medium to low [Bartoloni et al, 1989[Bartoloni et al, , 1999Gandolfo et al, 2003]. In addition, over the last few decades, Bolivia has experienced improvement in education, health, and income according to the HDI, which increased from 0.596 in 1990 to 0.729 in 2007.…”
Section: Introductionmentioning
confidence: 99%